The Effectiveness of Classical Music Therapy and Progressive Muscle Relaxation Therapy on Anxiety Levels - Jeny Ayu Ratri Semara Agni; Bambang Sarwono; Suyanta Suyanta (Midwifery and Nursing Research, 2020)
Background : Anxiety occurs when a person has difficulty in dealing with situations, problems and goals. One example of anxiety's situation is the anxiety experienced by students who will face the exam, the exam itself is an evaluation to assess the learning that has given the teachers to its students, the evaluation been assessed through exams. Efforts to reduced the anxiety one of them with progressive muscle relaxation therapy in which the body's response to anxiety will affect the mind and muscle tension. Then there is also an effort to decrease anxiety with music therapy to help express feelings and a positive influence on the condition and emotionsMethods : This research was conduct in March 2019, methods used quasy experimental design with time series approach. Instrument used to measure the level of anxiety with BAI (Beck Anxiety Inventory). Sampling technique using accidental sampling, with a sample of 40 respondents.Results : Statistical test results using independent t-test with p value 0,019 the first day, second day and third day 0.002 0.022 (p 0.05), which means there is a difference, then the average value obtained showed the lowest value between music therapy and therapy progressive muscle relaxation, which means no difference in effectiveness.Conclusion : There are differences in effectiveness where progressive muscle relaxation therapy is more effective than the classic music therapy in reducing anxiety levels in high school.